Raised intracranial pressure is frequent in untreated nonsyndromic unicoronal synostosis and does not correlate with severity of phenotypic features. - Eley, K; Johnson, D; Wilkie, A; Jayamohan, J; Richards, P; Wall, SA (2012)
BACKGROUND: In a small number of children with unicoronal synostosis, the phenotype is mild and the aesthetic benefit of surgical correction is potentially outweighed by surgical risk. Raised intracranial pressure, however, would necessitate intervention. The authors documented the incidence of raised intracranial pressure in children with mild features and/or parental reluctance to proceed directly to surgery. METHODS: A retrospective review of all children with (1) a clinical diagnosis of nonsyndromic unicoronal synostosis; (2) unicoronal synostosis confirmed on computed tomographic scanning; (3) negative family history for unicoronal synostosis; and (4) negative genetic screening (including P250R encoded by FGFR3, exons IIIa and IIIc in FGFR2 and TWIST1) was completed. RESULTS: Of the 80 children studied, seven (9 percent) underwent formal intracranial pressure monitoring because of a combination of mild clinical features (n = 4) and/or parental reluctance to proceed with surgery (n = 3). Intracranial pressure monitoring was reported as high in three (42 percent), borderline in two (29 percent), and normal in two patients (29 percent). The findings did not correlate with the degree of clinical deformation or age at presentation. There was little correlation with clinical and radiographic features of raised intracranial pressure in this genetically screened nonsyndromic group. CONCLUSIONS: High or borderline raised intracranial pressure was present in five of seven cases. The risk did not correlate with degree of deformity or age at presentation. Formal intracranial pressure monitoring should be considered in all children with unicoronal synostosis not proceeding directly to surgical intervention, in combination with routine long-term follow-up and repeated intracranial pressure monitoring where indicated. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, V.